El Dentascan: un programa de tomografía axial computarizada específico para estudios de maxilares - Herrera Rubio, Adriana María (Revista Estomatología, 1996)
A Computarized Tomography program for maxillaries appeard in 1987- The DentaScan or Reformated Multiplanigraph from maxillar axial sections can accomplish para-axial (perpendicular to the alveolar bone) and panoramic reconstructions permiting information of internal anatomic structures, density, high and real extention ofthe osseous bases. The present article describes the tecnical caracteristics ofthe program, advantages and aplications in Implantology, Pathology and Maxillofacial Surgery.